Imunoexpressão de LGR4 e β-CATENINA no câncer de estômago, metástases linfonodais e mucosa gástrica histologicamente normal - Souza, Susana Moreira (2018)
Gastric cancer is the fifth most common malignant neoplasm worldwide and the third leading cause of cancer mortality. The ineffectiveness of the therapy is probably due to the permanence of tumor stem cells that show some characteristics of normal stem cells. LGR4 and nuclear β-catenin are potential biomarkers related to carcinogenesis and tumor progression in stomach cancer. Aim: to evaluate the immunoexpression of LGR4 and β-catenin in primary gastric carcinomas, lymph node metastases and histologically normal gastric mucosa in the surgical margins of gastric primary tumors. Methods: a cross - sectional and observational study, based on 75 samples from gastrectomy by gastric carcinomas, performed at Walter Cantídio University Hospital of the Federal University of Ceará, Brazil, obtained through tissue microarray and immunohistochemistry. Chi-square, Fisher's exact test and Pearson's linear regression were used in this study. Results: LGR4 expression was greater in the histologically normal mucosa (basal third of the epithelial thickness) of the tumor surgical resection margin than in primary carcinomas, comparing the number of normal cases with positive tumor (in both intestinal and diffuse histotypes) . The number of cells stained in the normal mucosa was also much higher than in the positive (p<0.0001) tumor samples. Primary intestinal carcinomas showed greater positivity than the diffuse ones (59%, 13%, p <0.0001). Diffuse histotype tumors were more positive for LGR4 in lymph node implants than in their respective stomach lesions (p = 0.0242). The β-catenin membrane immunoexpression was universal in the normal mucosa and in 2/3 of the positive carcinomas (in both histotypes evaluated together). The difference was significant between diffuse carcinoma margins and respective tumors (p = 0.0007). In only one case of metastatic intestinal carcinoma nuclear β-catenin expression was observed. Most LGR4 positive cases were also stained for β-catenin membranes, but not the reverse (P <0.01). Conclusion: LGR4 is a biomarker frequently present in the histologically normal proliferative gastric mucosal layer and in carcinomas of the stomach, not specific for cancer cells and positively associated with cell proliferation. Its immunoexpression is more frequent and in a larger number of cells in normal tissues, when compared to tumor samples. The intestinal histotype and the presence of lymph node metastases (N> 0) are independent variables in the expression of LGR4. Expression of β-catenin in the junctional membrane-complex occurred predominantly in positive cases of gastric carcinomas, and immunostaining of this protein in the nucleus was extremely rare. LGR4 apparently influenced β-catenin membrane expression, but not the reverse.